Theory of l-systems as a framework for creating inflectional e-dictionaries - Kupriianov, Ye. (ХНУРЕ, 2022)
One of the main issues in modern e-lexicography is the creation and support of computer resources meant for teaching language grammar. Among them are electronic dictionaries of word inflection. The compilation of such dictionaries requires not only the choice of computer technologies, but also an appropriate theoretical basis for building a conceptual model that would formally represent the inflectional system of a particular language and serve as a basis for developing a respective dictionary database and interface. For the purposes of this research, such a basis is the theory of L-systems by the leading Ukrainian Academician Volodymyr A. Shyrokov. The author of the paper shares his own experience of using L-systems theory to work out a methodology and implement on its basis a number of inflectional e-dictionaries projects covering Spanish word inflection, English verb inflection, and noun inflection of the Inter-Slavic language. The theory of L-systems can be considered universal, so it is applicable to any other natural or even artificial language with a developed word inflection system. Однією з головних проблем сучасної електронної лексикографії є створення та підтримка комп'ютерних ресурсів, призначених для навчання граматики мови. Серед них – електронні словники відмінювання слів. укладання таких словників потребує не лише вибору комп'ютерних технологій, а й відповідного теоретичного підґрунтя для побудови концептуальної моделі, яка б формально репрезентувала флективну систему певної мови і слугувала основою для розробки відповідної словникової бази даних та інтерфейсу. У межах цього дослідження такою основою є теорія Л-систем провідного українського академіка Володимира Анатолійовича Широкова.
Keywords: computer lexicography; digital environment; inflectional e-dictionary; l-system